2012
DOI: 10.1063/1.3672065
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of L11 Co-Pt-Cu perpendicular anisotropic films with enhanced coercivity on glass substrate

Abstract: Structure and magnetic properties of L1 1 CoPtCu thin films sputter-deposited on glass substrates were studied. Perpendicular coercivity (H c\ ) was largely enhanced by the replacement of Co with Cu with x ¼ 23 and 26, the magnetic properties obtained was better than the film grown on MgO (111) substrates. The enhancement of H c\ existed in a wide range of film thickness from 2 to 40 nm. A maximum value of H c\ of 2.7 kOe appeared in the films with thickness of 4 nm. The results of surface morphology indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[6][7][8][9][10][11] Significant coercivity enhancement and ordering improvement of L1 1 CoPt films were demonstrated by adding Cu element and inserting Pt underlayer, respectively. 9-11 Later high-cost single crystal substrates such as MgO(111) and Al 2 O 3 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were replaced by glass and consequently largely increased the applicability of L1 1 CoPt films. [12][13][14][15] From the aforementioned studies, it is concluded that the in-situ heat treatment is necessary for formation of L1 1 CoPt phase.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11] Significant coercivity enhancement and ordering improvement of L1 1 CoPt films were demonstrated by adding Cu element and inserting Pt underlayer, respectively. 9-11 Later high-cost single crystal substrates such as MgO(111) and Al 2 O 3 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were replaced by glass and consequently largely increased the applicability of L1 1 CoPt films. [12][13][14][15] From the aforementioned studies, it is concluded that the in-situ heat treatment is necessary for formation of L1 1 CoPt phase.…”
mentioning
confidence: 99%
“…9-11 Later high-cost single crystal substrates such as MgO(111) and Al 2 O 3 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were replaced by glass and consequently largely increased the applicability of L1 1 CoPt films. [12][13][14][15] From the aforementioned studies, it is concluded that the in-situ heat treatment is necessary for formation of L1 1 CoPt phase. However, this method has to spend not only the thermal annealing energy but also long time for substrate cooling to ambient temperature, which induces grain growth during film deposition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, our previous studies indicate that the presence of CoPt(222) peak can be ascribed to the fundamental peak of L1 1 -type CoPt alloy. 13,14 Comparing Fig. 1(a) with that of Fig.…”
mentioning
confidence: 98%